2023
DOI: 10.1051/0004-6361/202244866
|View full text |Cite
|
Sign up to set email alerts
|

Probing the spacetime and accretion model for the Galactic Center: Comparison of Kerr and dilaton black hole shadows

Abstract: Context. In the 2017 observation campaign, the Event Horizon Telescope (EHT) for the first time gathered enough data to image the shadow of the super-massive black hole (SMBH) in M 87. Most recently in 2022, the EHT has published the results for the SMBH at the Galactic Center, Sgr A * . In the vicinity of black holes, the influence of strong gravity, plasma physics, and emission processes govern the behavior of the system. Since observations such as those carried out by the EHT are not yet able to unambiguous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…Observations of horizon-scale structures in Sgr A*, on one hand gave important constraints for theoretical models [226,252,253], on the other showed the feasibility of 1.3 mm VLBI techniques to peer into the innermost region of Sgr A*. This motivated theoretical advancement that allowed increasingly sophisticated general-relativistic simulations of accretion flows and radiative transfer of SMBH, reproducing realistic images for a great variety of near-horizon emission models, ATGs (see section 3.3) and alternative to BHs [253][254][255][256][257][258][259][260][261][262][263][264][265][266][267][268][269][270][271]. In parallel, VLBI studies of Sgr A* at 1.3 mm wavelength with progressively enhanced arrays, allowed a better characterization of the compact emission, its variability, significant polarization (which suggest the presence of intense magnetic field in the emitting region) and asymmetry in the image structure [272][273][274].…”
Section: Direct Observation Of Sgr A*mentioning
confidence: 99%
“…Observations of horizon-scale structures in Sgr A*, on one hand gave important constraints for theoretical models [226,252,253], on the other showed the feasibility of 1.3 mm VLBI techniques to peer into the innermost region of Sgr A*. This motivated theoretical advancement that allowed increasingly sophisticated general-relativistic simulations of accretion flows and radiative transfer of SMBH, reproducing realistic images for a great variety of near-horizon emission models, ATGs (see section 3.3) and alternative to BHs [253][254][255][256][257][258][259][260][261][262][263][264][265][266][267][268][269][270][271]. In parallel, VLBI studies of Sgr A* at 1.3 mm wavelength with progressively enhanced arrays, allowed a better characterization of the compact emission, its variability, significant polarization (which suggest the presence of intense magnetic field in the emitting region) and asymmetry in the image structure [272][273][274].…”
Section: Direct Observation Of Sgr A*mentioning
confidence: 99%
“…Additionally, the distribution function can be modified to account for a thermal and a magnetic contribution to the total energy [10,31,32,53]. That way, it is possible to control the amount of magnetically accelerated electrons and the distance of their point of injection into the jet from the central engine.…”
Section: The Kappa Modelmentioning
confidence: 99%
“…Alternative spacetime geometries are rarely investigated in full GRMHD and GRRT, and if so, the emission physics are based on a constant proton-to-electron temperature ratio and purely thermal radiation [68,69]. Only recently have advances been made to study the influence of emission models more akin to reality in an alternative spacetime [33,53]. The fundamental difficulties in finding deviations from the Kerr metric arise from the presence of greater astrophysical uncertainties.…”
Section: Emission Modeling In Non-kerr Spacetimesmentioning
confidence: 99%
“…GRMHD simulations of stringy black holes have been implemented in several works [24][25][26]. In [24], they demonstrated that a stronger jet is generated via the BZ process in stringy JCAP05(2024)101 rotating black holes.…”
Section: Introductionmentioning
confidence: 99%